Dietary Adherence and Glycemic Control among Patients with Type 2 Diabetes in Ga West Municipal Hospital - Ansah, G.A. (University of Ghana, 2019)
Background: Globally, diabetes is one of the major health crises. Ghana has been considerably affected by the double burden of communicable and non-communicable diseases, including high incidence of diabetes. The high incidence of diabetes recorded globally can be attributed to unhealthy diets. Objective: To assess dietary adherence and its association with glycemic control in adults with type 2 diabetes mellitus seeking treatment in Ga West Municipal Hospital Methods: A total number of 140 participants were selected from the diabetic clinic in the Ga West Municipal Hospital using a convenience sampling method. Descriptive statistics such as means ± SD, Tables, Frequency and Percentage were used to describe dependent and independent variables. Chi Square test was used to find associations between the glycemic control and independent variables. Bivariate and multivariable logistic regressions were used to determine the strength of association between glycemic control and dietary adherence, sociodemographic characteristics, lifestyle factors and perceived family support. A confidence interval of 95% was used to show statistical significance. Results: The percentage of participants with good glycemic control was 60% (n= 84). Majority of participants (74%) had good dietary knowledge. After controlling for the effect of age, sex, marital status, education, occupation and monthly income, lifestyle factors and family support, dietary adherence and referral to a dietician after being diagnosed with diabetes were found to be significantly associated with glycemic control. The odds of having good glycemic control was 12.3 times greater among respondents with good dietary adherence compared with those with poor dietary adherence (aOR=12.33, 95%CI: 3.64, 41.75; p<0.001). Respondents, referred to a dietician after being diagnosed with diabetes were 4.2 times more likely to have good glycemic control compared with those who were not referred (aOR=4.20, 95%CI: 1.47, 12.01; p=0.007). Conclusion: Dietary adherence and referral to a dietician after diagnosis are significant predictors of good glycemic control among people with type 2 diabetes presenting at the Ga West Municipal Hospital.
MPH.
Keywords: Diabetes Mellitus (DM); Glycemic Control; Type 2 Diabetes; Ga West Municipal Hospital